Changes In Education, Religion, Social, Economic, Culture, And Politics In Egypt Post-Napoleon Invasion - Hatib Rahmawan (Al-Misbah (Jurnal Islamic Studies), 2019)
The important role of Egypt in the Resurrection of the Islamic world is did not happen suddenly, but he had to go through a dark history, that was colonialized by Napoleon Bonaparte. Even though Napoleon ruled Egypt for three years, but his presence woke the Egyptian consciousness to progress and change. This paper aims to uncover the changes that occurred in Egypt in the fields of education, issues, economy, culture, and politics post-Napoleon invasion. From this, a main problem can be formulated as follows; How was the change in education, religion, social, economy, culture, and politics post-Napoleon invasion? This paper uses the liberary research method, which is combined with the model of writing history to reveal the relationship between historical facts with changes that occured. The important information obtained from this post-Napoleon study include; (1) in the field of education raises awareness of the underdevelopment of science, the development of various educational infrastructure, recognizing the importance of freedom and independence in the development of science; (2) Encouraging changes in perspectives and models of religion towards a more rational and solutions to the changing times; (3) in the social and cultural sphere the idea of equality (legalite) and equality between rulers and people was born and the development of war technology, weapons and military training adopted from France; (4) in the political field gave rise to the idea of nationalism and republican government; and (5) in the economic field to encourage the development of industrialization and agrarian reform.